Contenido de carbono en la biomasa aérea ene llaurel (cordia alliodora ruiz & Pav) y pachaco (Schizolobium parahybum) en tres localidades del Litoral ecuatoriano 2016 - 2017. - Lema Alvarado, Manuel Alexander (2017)
The present study was conducted in three localities of the Ecuadorian coast, it was quantified the content of carbon in tree plantations of Cordia Alliodora (laurel) and Schizolobium parahybum (the pachaco species) the locations under study (Santo Domingo, Balzar and Valencia), It was considered form factors in the plantations of 9 years of age, (10,000 m2 plots within which established four subplots of 500 m2), Dasometricas variables was evaluated and amount of carbon in the biomass allometric formulae of Clutter (1992), we used a block design and completely random. The highest average t CO2/ ha-1 was for the species pachaco. The dbh and basal area variables that showed significant differences were species-by-species and location. In the treatments by species the variables that showed more significant differences were biomass, biomass/ha and CO2/ha. The species of pachaco presented higher CO2 capture t ha-1 (86,1428) in the town of Santo Domingo and the laurel species (83,8345) of CO2 t ha-1 in the town of Santo Domingo.